Simulation-optimization model for one-way traffic reconfiguration. (July 2016) - Peng, Zixuan; Guan, Feng; Wang, Keming; Li, Ting; Yao, Baozhen
One-way traffic is a kind of traffic management measure with less investment, simple operation, and obvious effects. Considering some irrational one-way lane configurations currently in practice, a bi-level optimization programming model is proposed in this paper. The decision-making variable of the upper level model is the scheme of one-way traffic reconfiguration, and the optimization target is to minimize the total travel time. The lower level programming is an equilibrium traffic assignment model. The Shuffled Complex Evolution Algorithm (SCE-UA) and VisSim simulation are applied for the upper and lower models, respectively. A numerical test based on Dalian Harbour Plaza is employed to validate the proposed model. In the test, the effects of the current scheme, the scheme solved by the bi-level model using the SCE-UA and Frank-Wolfe algorithm, and the scheme proposed by this paper (simulation-optimization) are compared. As the results show, the bi-level programming model in this paper can perform well in reducing the total travel time of travelers and in improving traffic efficiency.